A high-performance positive electrode material with a phytic acid-modified single-walled carbon nanotube coating layer

CN122950438APending Publication Date: 2026-10-20YAOHE ERA (QINGDAO) ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611139447.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

(3)倍率性能差:高镍材料的电子导电率和离子扩散系数相对较低,在大电流密度下容量快速下降

Benefits of technology

(1)通过植酸修饰单壁碳纳米管复合包覆层,构建了高效的电子-离子双传输网络,同时体相P掺杂降低Li+扩散势垒。在5C高倍率下,本发明正极材料的放电比容量≥165mAh/g,远高于未改性高镍材料和单一包覆改性样品。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1785316507522-000001
    Figure REF-OBJ-1785316507522-000001
  • Figure REF-OBJ-1785316507522-000002
    Figure REF-OBJ-1785316507522-000002
  • Figure REF-OBJ-1785316507522-000003
    Figure REF-OBJ-1785316507522-000003
Patent Text Reader

Abstract

This invention discloses a high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating, belonging to the field of lithium-ion battery cathode material technology, and solving the problems of insufficient conductivity, poor interface stability, and structural degradation in high-nickel ternary cathode materials. The cathode material includes a cathode core and a composite coating layer covering its surface. The composite coating layer contains phytic acid-modified single-walled carbon nanotubes, and the cathode core bulk phase contains phosphorus elements distributed in a concentration gradient from the interface between the composite coating layer and the cathode core into the core interior. The preparation method includes: acidification treatment of the single-walled carbon nanotubes; dispersing the acidified single-walled carbon nanotubes in an organic solvent and adding phytic acid; adding the cathode core to the dispersion and mixing; filtering, drying, and calcining. This invention achieves synergistic effects of surface conductive network construction, interface protection, and bulk lattice stability, effectively improving the material's rate performance, cycle stability, and high-temperature and high-pressure adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode material technology, specifically a high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating. Background Technology

[0002] High-nickel ternary cathode materials (such as High-nickel ternary materials, due to their high specific capacity (≥200mAh / g) and high energy density, have become core cathode materials for power batteries. However, high-nickel ternary materials still face the following prominent problems in practical applications: (1) Structural instability: High-nickel materials are unstable during charging and discharging, especially under high voltage. Redox reactions lead to the loss of lattice oxygen, accompanied by the H2-H3 phase transition, causing drastic volume shrinkage and microcracks in the particles, resulting in a sharp decline in cycle performance. (2) Severe interfacial side reactions: residual alkali on the surface of high-nickel materials ( It reacts with the electrolyte to form a thick positive electrode electrolyte interface film with high impedance, which consumes active lithium and increases polarization. (3) Poor rate performance: High-nickel materials have relatively low electronic conductivity and ion diffusion coefficient, and their capacity decreases rapidly under high current density.

[0003] To improve the above problems, existing technologies often employ surface coating with metal oxides (such as...) ), fluorides (such as LiF), phosphates (such as However, most coating layers have poor ionic / electronic conductivity, hindering Li... + Transmission, on the contrary, leads to impaired rate performance. Phytic acid (inositol hexaphosphate, PA), as a phosphorus-containing organic acid, can chelate with metal ions, but its electronic conductivity is low when coated alone, and its polarization is large at high rates, resulting in limited improvement in rate performance. Single-walled carbon nanotubes (SWCNTs) have excellent conductivity and mechanical flexibility, but their dispersibility is poor and they are prone to agglomeration when directly coated, and their bonding force with high-nickel surfaces is weak, which prevents them from fully exerting their conductive network function.

[0004] Therefore, how to simultaneously solve the problems of insufficient conductivity, poor interface stability, and structural degradation in high-nickel ternary cathode materials, and achieve conductive network construction and Li + The synergistic optimization of rapid transmission, lattice stability, and other factors remains a critical technical challenge to be addressed in this field. Summary of the Invention

[0005] To address the shortcomings of the existing technology, the present invention aims to provide a high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer, thereby solving the problems mentioned in the background art.

[0006] To achieve the above objectives, a specific embodiment of the present invention provides a high-performance cathode material with a phytate-modified single-walled carbon nanotube coating layer, comprising a cathode material core and a composite coating layer covering the surface of the cathode material core; the composite coating layer contains phytate-modified single-walled carbon nanotubes; the bulk phase of the cathode material core contains phosphorus, and the phosphorus is doped in a concentration gradient distribution from the contact interface between the composite coating layer and the cathode material core toward the interior of the cathode material core.

[0007] In addition, the high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer proposed in this application may also have the following additional technical features: In one embodiment of this application, amorphous lithium phosphate and lithium pyrophosphate are present at the contact interface between the composite coating layer and the cathode material core.

[0008] In one embodiment of this application, the cathode material core is a high-nickel ternary cathode material, whose chemical formula is [chemical formula missing]. ,in ; or the core of the positive electrode material is .

[0009] In one embodiment of this application, the phytic acid in the composite coating layer is modified onto the surface of the single-walled carbon nanotube via non-covalent bonds.

[0010] In one embodiment of this application, the amorphous lithium phosphate and lithium pyrophosphate are in-situ products generated by the neutralization reaction of phytic acid with residual alkali on the surface of the cathode material core.

[0011] In one embodiment of this application, the thickness of the composite coating layer is 10~50nm; the mass ratio of the phytic acid to the single-walled carbon nanotube is 10:5~10:1.

[0012] In one embodiment of this application, the single-walled carbon nanotubes interweave with each other in the composite coating layer to form a three-dimensional conductive network.

[0013] A method for preparing a high-performance cathode material includes the following steps: Step S1: Place the single-walled carbon nanotubes in a mixed acid for acidification treatment, and after washing with water and drying, obtain acidified single-walled carbon nanotubes. Step S2: Disperse the acidified single-walled carbon nanotubes in an organic solvent, add phytic acid and perform dispersion treatment to obtain a phytic acid modified single-walled carbon nanotube dispersion. Step S3: Add the cathode material core to the phytic acid modified single-walled carbon nanotube dispersion and mix them to allow the composite coating layer precursor to adhere to the surface of the cathode material core. Step S4: After solid-liquid separation and drying of the product obtained in step S3, calcination is performed in an oxygen-containing atmosphere to obtain the high-performance cathode material.

[0014] In one embodiment of this application, the mixed acid in step S1 is a mixture of concentrated sulfuric acid and concentrated nitric acid, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3:1.

[0015] In one embodiment of this application, the calcination temperature in step S4 is 500~600℃, and the calcination time is 2~6 hours.

[0016] The advantages of this invention compared to existing technologies are: (1) By modifying the single-walled carbon nanotube composite coating layer with phytic acid, a highly efficient electron-ion dual transport network was constructed, while bulk P doping reduced Li + Diffusion barrier. At a high rate of 5C, the discharge specific capacity of the cathode material of this invention is ≥165mAh / g, which is much higher than that of unmodified high-nickel materials and single-coated modified samples.

[0017] (2) Under 1C charge-discharge conditions and a voltage range of 2.8~4.45V, after 300 cycles, the capacity retention rate is ≥80%, while the capacity retention rate of conventional high-nickel materials under the same conditions is usually less than 60%. This is attributed to the fact that the composite coating layer effectively inhibits the excessive growth of CEI, reduces particle microcracks, and stabilizes the crystal structure.

[0018] (3) The present invention generates phytic acid by reacting with residual alkali. The layer effectively isolates the high-nickel surface from direct contact with the electrolyte, suppressing side reactions; at the same time, bulk P doping stabilizes the transition metal layer, suppresses volume distortion caused by the H2-H3 phase transition, and improves structural and thermal stability under high temperature and high pressure conditions.

[0019] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a flowchart illustrating the process of a high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating in one embodiment of the present invention. Figure 2 This is a schematic diagram of the structure of a high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer in one embodiment of the present invention; Figure 3 This is a flowchart illustrating the battery assembly and testing process of a high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating, according to one embodiment of the present invention.

[0022] Explanation of reference numerals in the attached figures: 1. Cathode material core; 2. Composite coating layer; 3. Phytic acid; 4. Single-walled carbon nanotubes. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] Example 1 like Figures 1 to 3 As shown, this embodiment provides a high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer, comprising a cathode material core 1 and a composite coating layer 2 covering the surface of the cathode material core 1. The composite coating layer 2 contains phytic acid-modified single-walled carbon nanotubes 4. The bulk phase of the cathode material core 1 contains phosphorus, and the phosphorus is doped in a concentration gradient distribution from the contact interface between the composite coating layer 2 and the cathode material core 1 toward the interior of the cathode material core 1.

[0025] The cathode material core 1 is a high-nickel ternary cathode material, preferably... (abbreviated as NCM811) or (abbreviated as NCA), its particle diameter is 5~15μm, and its specific surface area is 0.5~2.0m². 2 / g. The composite coating layer 2 is tightly adhered to the surface of the cathode material core 1, forming a contact interface between the two. At this contact interface, due to the phosphate groups of phytic acid 3 reacting with the residual alkali (LiOH and ) on the surface of the cathode material core 1, A neutralization reaction occurs, and amorphous lithium phosphate is generated in situ. ) and lithium pyrophosphate ( These two amorphous phosphates exist in thin layers, providing both a rapid lithium-ion transport channel and acting as an insulator between the electrolyte and the surface of the cathode material core 1. Simultaneously, during subsequent heat treatment, some phosphorus from phytic acid 3 diffuses into the cathode material core 1, forming a concentration gradient doping distribution from the contact interface inwards within the bulk phase of the cathode material core 1. Specifically, the phosphorus concentration is highest at the contact interface and gradually decreases radially until it reaches a stable value in the central region of the cathode material core 1. This concentration gradient doping effectively reduces the diffusion barrier of lithium ions in the bulk phase of the cathode material core 1, stabilizing the crystal structure.

[0026] In the composite coating layer 2, phytic acid 3 is bonded via non-covalent bonds (including...) The surface of single-walled carbon nanotubes (SUVs) 4 is modified with phytic acid (3) through stacking and hydrogen bonding, allowing the SUVs 4 to be uniformly dispersed in the organic solvent and preventing aggregation. The mass ratio of phytic acid 3 to SUVs 4 is 10:5 to 10:1. The SUVs 4 intertwine in the composite coating layer 2, forming a continuous, flexible, and highly conductive three-dimensional conductive network. This network covers the surface of the cathode material core 1, providing a high-speed electron transport channel during charging and discharging. Simultaneously, its mechanical flexibility buffers the volume expansion of the cathode material core 1 during charging and discharging, suppressing the generation of microcracks in the particles. The thickness of the composite coating layer 2 is 10-50 nm, preferably 30 nm. If the thickness is less than 10 nm, the coating layer cannot completely cover the surface of the cathode material core 1, resulting in insufficient interface protection. If the thickness is greater than 50 nm, the impedance of the composite coating layer 2 increases, leading to a decrease in lithium-ion transport efficiency.

[0027] The preparation method of the above-mentioned cathode material includes the following steps: Step S1: Acidification Pretreatment of Single-Walled Carbon Nanotubes (SUCs). SUCs 4 are added to a mixed acid for acidification. Specifically, 1 g of SUCs (purity >95%, diameter 0.8~1.2 nm, length 5~30 μm) is weighed and added to 100 mL of a mixed acid solution of concentrated sulfuric acid (98% by mass) and concentrated nitric acid (68% by mass), with a volume ratio of 3:1. The mixture is refluxed and stirred at 100 °C for 4 hours to introduce oxygen-containing functional groups such as carboxyl and hydroxyl groups onto the surface of the SUCs 4, thereby increasing the binding sites for subsequent non-covalent modification with phytic acid 3. After the reaction, the mixture is cooled to room temperature, slowly poured into deionized water, filtered using a sintered glass funnel, and then repeatedly washed with deionized water until the pH of the filtrate reaches 7. The filtrate is then vacuum-dried at 80 °C for 12 hours to obtain acidified SUCs.

[0028] Step S2: Preparation of phytic acid-modified single-walled carbon nanotube dispersion. 0.02 g of the acidified single-walled carbon nanotubes were added to 100 mL of ethanol and ultrasonically dispersed for 30 minutes (ultrasonic power 300 W, frequency 40 kHz) to ensure thorough dispersion of the acidified single-walled carbon nanotubes in the ethanol solvent. Then, 0.1 g of phytic acid 3 (70% aqueous solution) was added, and ultrasonic treatment continued for 2 hours. During this process, phytic acid 3... Non-covalent interactions such as stacking and hydrogen bonding are used to modify the surface of acidified single-walled carbon nanotubes, forming a uniform and stable phytic acid-modified single-walled carbon nanotube dispersion. The mass ratio of phytic acid 3 to single-walled carbon nanotube 4 is approximately 5:1.

[0029] Step S3, Coating. Weigh 10g of cathode material core 1 (NCM811, D50=10μm) and add it to the above phytic acid modified single-walled carbon nanotube dispersion. Stir at 500rpm for 3 hours to make the composite coating layer precursor uniformly adhere to the surface of cathode material core 1.

[0030] Step S4, heat treatment. The above mixture is filtered, dried at 80°C for 4 hours, and then heated to 550°C in a tube furnace under air atmosphere at a heating rate of 5°C / min, held for 4 hours, and naturally cooled to room temperature. During calcination, phytic acid 3 decomposes and neutralizes with the residual alkali on the surface of the cathode material core 1, generating amorphous lithium phosphate and lithium pyrophosphate in situ at the contact interface; simultaneously, some phosphorus diffuses into the interior of the cathode material core 1, achieving a concentration gradient doping from the contact interface towards the interior. In addition, single-walled carbon nanotubes 4 interweave to form a three-dimensional conductive network in the composite coating layer 2. Finally, a high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer is obtained.

[0031] The process of using the obtained positive electrode material in lithium-ion batteries is as follows: The positive electrode material is mixed with conductive agent Super P and binder PVDF at a mass ratio of 8:1:1, and N-methylpyrrolidone is used as a solvent to prepare a slurry. This slurry is coated onto an aluminum foil current collector, vacuum dried, rolled, and cut into positive electrode sheets. Graphite is used as the negative electrode, Celgard 2400 is used as the separator, and 1M... A 1:1:1 volume ratio electrolyte was used to assemble a coin cell. During charging and discharging, the three-dimensional conductive network constructed by the single-walled carbon nanotubes 4 in the composite coating layer 2 provided a high-speed electron transport path, significantly reducing electrode impedance; simultaneously, the reaction of phytic acid 3 with residual alkali to generate... The layer provides a fast channel for lithium ions, and the phosphorus element doped in the bulk phase with a concentration gradient reduces the lithium ion diffusion barrier. The synergistic effect of these three elements gives the cathode material excellent rate performance, cycle stability and high temperature and high pressure adaptability.

[0032] Example 2 This embodiment is basically the same as the structure and working principle of Embodiment 1. The difference is that: there are amorphous lithium phosphate and lithium pyrophosphate at the contact interface between the composite coating layer 2 and the cathode material core 1. The amorphous lithium phosphate and lithium pyrophosphate are in-situ generated products of the neutralization reaction between phytic acid 3 and the residual alkali on the surface of the cathode material core 1.

[0033] Specifically, during the preparation process of the cathode material core 1, a small amount of LiOH and... inevitably remain on its surface. These residual bases undergo a neutralization reaction upon contact with phytic acid 3, as shown in the following equation: (Preliminary chelation) → generated after calcination and decomposition .

[0034] Amorphous lithium phosphate and lithium pyrophosphate exist in nanoscale thin layers at the interface between the composite coating layer 2 and the cathode material core 1. This thin layer possesses excellent lithium-ion conductivity and physically isolates the surface of the cathode material core 1 from the electrolyte, preventing direct contact between the electrolyte and the cathode material core 1 surface and potential side reactions, thereby suppressing excessive growth of the cathode-electrolyte interface film. In this embodiment, by controlling the amount of phytic acid 3 added and the calcination process parameters, the content of amorphous lithium phosphate and lithium pyrophosphate at the interface is kept within a reasonable range, effectively protecting the interface without consuming excessive active lithium due to over-reaction.

[0035] Example 3 This embodiment is basically the same as Embodiment 1 in structure and working principle, the difference being that: the cathode material core 1 is a high-nickel ternary cathode material, its chemical formula is... Where x ≥ 0.8. Specifically, the range of x is 0.8~0.95, the range of y is 0.02~0.15, and the range of 1-xy is 0.02~0.15. When x = 0.8, y = 0.1, and 1-xy = 0.1, the corresponding... When x = 0.83, y = 0.1, and 1 - xy = 0.07, it corresponds to NCM83; when x = 0.88, y = 0.1, and 1 - xy = 0.02, it corresponds to NCM88. Furthermore, the cathode material core 1 can also be... In the above chemical formula, the total molar number of transition metal elements is 1, and the molar fraction of Ni element x ≥ 0.8, ensuring that the cathode material has a high specific capacity. In this embodiment, regardless of which of the above high-nickel ternary cathode materials is used as the cathode material core 1, phosphorus gradient doping and interface protection can be achieved by modifying the composite coating layer 2 composed of single-walled carbon nanotubes 3 with phytic acid 3, thereby obtaining excellent electrochemical performance.

[0036] Example 4 The structure and working principle of this embodiment are basically the same as those of Embodiment 1. The difference is that the thickness of the composite coating layer 2 is 10~50nm, and the mass ratio of phytic acid 3 to single-walled carbon nanotubes 4 is 10:5~10:1.

[0037] Specifically, the thickness of the composite coating layer 2 can be adjusted by controlling the solid-liquid ratio of the cathode material core 1 and the phytic acid-modified single-walled carbon nanotube dispersion in step S3, the stirring time, and the calcination temperature and time in step S4. When the thickness of the composite coating layer 2 is 10 nm, it can basically cover the surface of the cathode material core 1, providing minimum interface protection; when the thickness is 30 nm, it can achieve the best balance between interface protection and lithium-ion transport; when the thickness is 50 nm, it can provide stronger interface protection and a more sufficient phosphorus doping source, but if it exceeds 50 nm, the lithium-ion transport impedance increases. The preferred mass ratio of phytic acid 3 to single-walled carbon nanotubes 4 is 2:1 to 10:1 (i.e., 10:5 to 10:1). If the ratio of phytic acid 3 is less than 10:5 (i.e. 2:1), the dispersion modification effect of phytic acid 3 is insufficient, the single-walled carbon nanotubes 4 are not sufficiently dispersed and are prone to agglomeration; if the ratio of phytic acid 3 is greater than 10:1, there will be an excess of phytic acid 3 in the composite coating layer 2, which will excessively consume the active lithium on the surface of the cathode material core 1 during calcination, and the excessive decomposition products of phytic acid 3 will hinder lithium ion transport and reduce electrochemical performance.

[0038] Example 5 The structure and working principle of this embodiment are basically the same as those of Embodiment 1. The difference is that the single-walled carbon nanotubes 4 intertwine with each other in the composite coating layer 2 to form a three-dimensional conductive network.

[0039] Specifically, single-walled carbon nanotubes 4, due to their high aspect ratio (length 5~30 μm, diameter 0.8~1.2 nm) and excellent flexibility, are randomly oriented and interwoven in the composite coating layer 2, forming a continuous three-dimensional conductive network structure similar to a sponge. This three-dimensional conductive network covers the entire surface of the cathode material core 1 and extends into the gaps between the particles of the cathode material core 1. During charging, electrons generated by the cathode material core 1 are rapidly transferred to the current collector through this three-dimensional conductive network, effectively reducing the ohmic impedance of the electrode. During discharging, electrons are rapidly transferred from the current collector to the cathode material core 1 through this three-dimensional conductive network, ensuring efficient electron transport at high rates. Simultaneously, this three-dimensional conductive network possesses excellent mechanical flexibility. When the cathode material core 1 undergoes volume expansion and contraction during charging and discharging, the single-walled carbon nanotubes 4 can absorb and buffer the stress generated by the volume changes, effectively suppressing the propagation of microcracks in the particles of the cathode material core 1, thereby improving cycle stability.

[0040] Example 6 The preparation method of this embodiment is basically the same as that of Example 1, except that: in step S1, the mixed acid is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; in step S4, the calcination temperature is 500~600℃ and the calcination time is 2~6 hours.

[0041] Specifically, in step S1, when acidification is performed using a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, oxygen-containing functional groups such as carboxyl and hydroxyl groups can be effectively introduced onto the surface of the single-walled carbon nanotubes 4. The acid treatment conditions are mild and moderate, ensuring sufficient introduction of functional groups while avoiding excessive damage to the carbon skeleton of the single-walled carbon nanotubes 4. If the volume ratio of concentrated sulfuric acid to concentrated nitric acid deviates from 3:1, for example, if it is greater than 3:1 (e.g., 5:1), the proportion of concentrated sulfuric acid is too high, resulting in excessive oxidizing power, which may lead to excessive etching of the tube wall of the single-walled carbon nanotubes 4 and a decrease in conductivity. If it is less than 3:1 (e.g., 2:1), the proportion of concentrated nitric acid is too high, the acidification effect is insufficient, the introduction of surface functional groups is limited, and there are insufficient non-covalent modification binding sites for subsequent phytic acid 3. In step S4, the calcination temperature is controlled within the range of 500~600℃, preferably 550℃. If the calcination temperature is below 500℃, phytic acid 3 decomposes insufficiently, resulting in insufficient driving force for phosphorus diffusion into the bulk phase of the cathode material core 1, making effective concentration gradient doping impossible. If the calcination temperature is above 600℃, the core 1 of the cathode material undergoes excessive grain growth, increasing the lithium-ion diffusion path and consequently decreasing electrochemical performance. The calcination time should be controlled within the range of 2–6 hours, preferably 4 hours. If the calcination time is less than 2 hours, phosphorus diffusion is insufficient, leading to inadequate gradient doping depth. If the calcination time exceeds 6 hours, energy consumption increases, and excessive grain growth may occur. By controlling the combination of the above-mentioned calcination temperature and time, the phosphorus doping concentration and gradient distribution can be precisely controlled, thereby achieving optimal electrochemical performance.

[0042] Example 7 The preparation method of this embodiment is basically the same as that of Example 1, except that the organic solvent used in step S2 is selected from at least one of ethanol, N-methylpyrrolidone and tetrahydrofuran.

[0043] Specifically, acidified single-walled carbon nanotubes exhibit good dispersibility in all the aforementioned organic solvents. Ethanol has the advantages of low toxicity and low cost, making it suitable for conventional preparation; N-methylpyrrolidone has a high boiling point and good solubility, making it suitable for scenarios requiring high dispersion temperatures and long dispersion times; tetrahydrofuran has a low boiling point and high volatility, making it suitable for scenarios requiring rapid drying. In actual preparation, suitable organic solvents can be selected according to process requirements, or two or more of them can be mixed to achieve the best dispersion effect and process economy. The other process steps, process parameters, and the performance of the resulting cathode material in this embodiment are basically the same as in Example 1.

[0044] Example 8 The preparation method of this embodiment is basically the same as that of embodiment 1, except that the mixing process in step S3 is ball milling, the ball milling speed is 200~400 rpm, the ball-to-material ratio is 5:1~10:1, and the ball milling time is 1~5 hours, so that the composite coating layer precursor is uniformly attached to the surface of the cathode material core 1.

[0045] Specifically, ball milling, through the mechanical collision and friction between the grinding balls and the cathode material core 1, promotes a more uniform and denser adhesion of the phytic acid-modified single-walled carbon nanotube dispersion to the surface of the cathode material core 1. This is particularly suitable for cathode material core 1 particles with small diameters or complex surface morphologies. In this embodiment, the ball mill jar is lined with zirconium oxide, and the grinding balls are zirconium oxide balls (a mixture of 3mm and 5mm diameter balls) at a ball-to-material ratio of 8:1. The ball milling speed is 300 rpm, and the milling time is 3 hours. After ball milling, the mixture is removed for subsequent filtration, drying, and calcination. The composite coating precursor after ball milling exhibits more uniform and dense adhesion, and the electrochemical performance of the resulting cathode material is essentially equivalent to or slightly improved compared to Example 1.

[0046] Example 9 This embodiment provides a lithium-ion battery comprising the positive electrode material described in any of the above embodiments. The lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The positive electrode sheet comprises the high-performance positive electrode material with a phytic acid-modified single-walled carbon nanotube coating layer described above. Specifically, the positive electrode sheet is prepared by mixing the positive electrode material with a conductive agent and a binder to form a slurry, which is then coated onto an aluminum foil current collector. The negative electrode sheet comprises a graphite negative electrode material. The separator is a porous polyolefin separator, such as Celgard 2400. The electrolyte is a solution of lithium salt dissolved in an organic solvent; the lithium salt is lithium hexafluorophosphate, and the organic solvent is a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate. This lithium-ion battery exhibits excellent rate performance and cycle stability at both 25°C and -20°C.

[0047] The technical solutions in the above embodiments of this application solve the dispersion problem of single-walled carbon nanotubes 4 in organic solvents by non-covalent modification of single-walled carbon nanotubes 4 with phytic acid 3, so that single-walled carbon nanotubes 4 are uniformly distributed on the surface of the cathode material core 1 and form a three-dimensional conductive network, which effectively reduces the electrode impedance and improves the electron transport efficiency at high rates. At the same time, phytic acid 3 and the residual alkali on the surface of the cathode material core 1 generate amorphous lithium phosphate and lithium pyrophosphate in situ at the contact interface, which isolates the direct contact between the electrolyte and the cathode surface and suppresses side reactions. In addition, the concentration gradient doping of phosphorus from the contact interface to the bulk phase of the cathode material core 1 stabilizes the crystal structure and reduces the lithium ion diffusion barrier, thereby synergistically achieving high discharge capacity, long cycle life and structural stability under high temperature and high pressure conditions.

[0048] Obviously, the above-described embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention also intends to include these modifications and variations.

Claims

1. A high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating, characterized in that, It includes a positive electrode material core (1) and a composite coating layer (2) covering the surface of the positive electrode material core (1). The composite coating layer (2) contains phytic acid (3) modified single-walled carbon nanotubes (4). The bulk phase of the cathode material core (1) contains phosphorus, and the phosphorus is doped in a concentration gradient from the contact interface between the composite coating layer (2) and the cathode material core (1) toward the interior of the cathode material core (1).

2. The high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer according to claim 1, characterized in that, Amorphous lithium phosphate and lithium pyrophosphate are present at the interface between the composite coating layer (2) and the cathode material core (1).

3. The high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer according to claim 1, characterized in that, The cathode material core (1) is a high-nickel ternary cathode material with the chemical formula: ,in ; or the cathode material core (1) is .

4. The high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating as described in claim 1, characterized in that, In the composite coating layer (2), the phytic acid (3) is modified on the surface of the single-walled carbon nanotube (4) by non-covalent bonds.

5. The high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer according to claim 2, characterized in that, The amorphous lithium phosphate and lithium pyrophosphate are in-situ products generated by the neutralization reaction between the phytic acid (3) and the residual alkali on the surface of the cathode material core (1).

6. The high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating as described in claim 1, characterized in that, The thickness of the composite coating layer (2) is 10~50nm; the mass ratio of the phytic acid (3) to the single-walled carbon nanotube (4) is 10:5~10:

1.

7. The high-performance cathode material with a phytic acid-modified single-walled carbon nanotube coating layer according to claim 1, characterized in that, The single-walled carbon nanotubes (4) intertwine with each other in the composite coating layer (2) to form a three-dimensional conductive network.

8. A method for preparing a high-performance cathode material as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step S1: The single-walled carbon nanotubes (4) are placed in a mixed acid for acidification treatment. After washing with water and drying, acidified single-walled carbon nanotubes are obtained. Step S2: Disperse the acidified single-walled carbon nanotubes in an organic solvent, add phytic acid (3) and perform dispersion treatment to obtain a phytic acid modified single-walled carbon nanotube dispersion. Step S3: Add the cathode material core (1) to the phytic acid modified single-walled carbon nanotube dispersion and mix them to make the composite coating layer precursor adhere to the surface of the cathode material core (1). Step S4: After solid-liquid separation and drying of the product obtained in step S3, calcination is performed in an oxygen-containing atmosphere to obtain the high-performance cathode material.

9. The preparation method according to claim 8, characterized in that, The mixed acid mentioned in step S1 is a mixture of concentrated sulfuric acid and concentrated nitric acid, with a volume ratio of 3:1 between the concentrated sulfuric acid and the concentrated nitric acid.

10. The preparation method according to claim 8, characterized in that, The calcination temperature in step S4 is 500~600℃, and the calcination time is 2~6 hours.